2015
DOI: 10.1007/s11469-015-9598-2
|View full text |Cite
|
Sign up to set email alerts
|

Problem Drinking, Gambling and Eating Among Undergraduate University Students. What are the Links?

Abstract: Problematic drinking, gambling and eating are elevated among undergraduate university students but our understanding of how they are linked is limited. In this study, drinking, gambling and eating were assessed across a number of dimensions: drinking and gambling involvement, associated negative consequences, impairment of control, and motives; and disordered eating concerns and behaviours, loss of control over eating, and eating expectancies (N = 301). Canonical correlation analysis revealed that drinking and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…Moreover, the results cast further doubts on the role of SR within the context of EDs. Although the SOT has been used in the domain of substance abuse before (van Hemel‐Ruiter et al ., ) and parallels have often been drawn between EDs and substance abuse (Loxton & Dawe, ; Hodgins, von Ranson, & Montpetit, ), the present findings suggest that there are also important differences between addiction and EDs with regard to the attentional processes involved. While attentional bias towards signals predicting reward has been found to be positively associated with substance abuse (van Hemel‐Ruiter et al ., ), it seems that both attentional bias towards signals predicting punishment and reward might be positively associated with disordered eating, depending on which specific ED is considered (AN‐R in which attentional disengagement towards signals predicting reward seems to play an important role or B/P in which attentional disengagement towards signals predicting punishment seems to be a key factor).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Moreover, the results cast further doubts on the role of SR within the context of EDs. Although the SOT has been used in the domain of substance abuse before (van Hemel‐Ruiter et al ., ) and parallels have often been drawn between EDs and substance abuse (Loxton & Dawe, ; Hodgins, von Ranson, & Montpetit, ), the present findings suggest that there are also important differences between addiction and EDs with regard to the attentional processes involved. While attentional bias towards signals predicting reward has been found to be positively associated with substance abuse (van Hemel‐Ruiter et al ., ), it seems that both attentional bias towards signals predicting punishment and reward might be positively associated with disordered eating, depending on which specific ED is considered (AN‐R in which attentional disengagement towards signals predicting reward seems to play an important role or B/P in which attentional disengagement towards signals predicting punishment seems to be a key factor).…”
Section: Discussionsupporting
confidence: 74%
“…While attentional bias towards signals predicting reward has been found to be positively associated with substance abuse (van Hemel‐Ruiter et al ., ), it seems that both attentional bias towards signals predicting punishment and reward might be positively associated with disordered eating, depending on which specific ED is considered (AN‐R in which attentional disengagement towards signals predicting reward seems to play an important role or B/P in which attentional disengagement towards signals predicting punishment seems to be a key factor). This is in line with previous results indicating that different motives are involved in alcohol use compared with motives underlying disordered eating (Hodgins et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…The empirical literature has consistently found that of all the motives, coping motives has been robustly associated with problematic engagement of addictive behaviors, including both behavioral and substance addictions ( 56 , 126 ). Moreover, our recent work suggests that common motives underlie comorbid alcohol, gambling, and eating problems ( 127 , 128 ).…”
Section: Expectancies and Motivesmentioning
confidence: 99%
“…We combined the ten factors and the gender of the subjects as the research objects. Data mining techniques are used to study the relationship between mental health factors and the health factors (Hodgins, D. C., et al 2015).…”
Section: Experiments and Analysesmentioning
confidence: 99%